Activation of TRPV4 Increases Neovascularization of Rat Prefabricated Flaps - Bae, Jinhong; Wang, Zhichao; Li, Haizhou; Lu, Lin; Yu, Qingxiong; Li, Qingfeng; Tao, Zan (Journal of Reconstructive Microsurgery, 2018)
Background Inadequate neovascularization is a major risk factor that can lead to subsequent necrosis of prefabricated flaps. Recent evidence indicates that transient receptor potential cation channel, subfamily V, member 4 (TRPV4) activates growth and remodeling of collateral arteries in ischemia tissues by responding to elevated fluid shear stress (FSS). Therefore, we evaluated whether TRPV4 could increase neovascularization in prefabricated flaps in a rat model.Methods Rat prefabricated skin flaps were created by ligating the right femoral vascular pedicle and implanting it underneath abdominal flaps. Thirty-six male Sprague–Dawley rats were randomly assigned to three groups with different solutions injected subcutaneously in the implantation site around the pedicle: injected with normal saline as the control group; injected with 4α-Phorbol 12,13-didecanoate (4αPDD), a specific TRPV4 activator, as the 4αPDD group; or injected with ruthenium red (RR), a TRPV-blocker, as the RR group. Neovascularization was evaluated by laser speckle contrast imaging (FLPI), histological staining, and enzyme-linked immunosorbent assay (ELISA) within two weeks. Afterwards, the abdominal island flaps were completely elevated and sutured back. The flap viability and survival area were examined on day 7.Results A larger area of flap survival, higher capillary densities, and higher von Willebrand factor (vWF) expression were observed in the 4αPDD group in comparison to those in the other two groups. The secretion of vascular endothelial growth factor (VEGF), but not basic fibroblast growth factor (bFGF), was significantly elevated in the 4αPDD group.Conclusion Activation of TRPV4 using 4αPDD can significantly increase the survival of prefabricated flaps via neovascularization inducement, possibly through VEGF secretion enhancement. TRPV4 serves as a potential therapeutic neovascularization target in prefabricated flaps.
Keywords: TRPV4; prefabricated flaps; neovascularization; vascular endothelial growth factor